Abnormal liver tests in patients hospitalized with Coronavirus disease 2019: Should we worry?. (21st June 2020) - Meszaros, Magdalena; Meunier, Lucy; Morquin, David; Klouche, Kada; Fesler, Pierre; Malezieux, Emilie; Makinson, Alain; Le Moing, Vincent; Reynes, Jacques; Pageaux, Georges‐Philippe
Abstract: While several studies from China have reported COVID‐19‐related liver injury, there are currently no data on liver dysfunction in hospitalized COVID‐19 patients in Europe. The aim of this study was to describe the prevalence and predictive value of abnormal liver function in patients hospitalized with COVID‐19. This was a retrospective cohort study of confirmed COVID‐19 patients hospitalized in two referral hospitals in France. Clinical, biological and radiological data were collected and analysed. In all, 234 patients confirmed to have COVID‐19 by RT‐PCR were included. Liver function was abnormal in 66.6% of patients on admission. In multivariate logistic regression, abnormal liver test on admission were associated with in‐hospital aggravation (OR = 4.1, 95% CI 1.5‐10.8; P  = .004) and mortality (OR 3.3; 95% CI = 1.04‐10.5; P  = .04). This study of liver tests in a European COVID‐19 population confirms a high prevalence of abnormal liver tests on admission that are predictive of severe disease course and higher in‐hospital mortality.